Urban AI in China: Social control or hyper-capitalist development in the post-smart city? - Marvin, Simon; While, Aidan; Chen, Bei; Kovacic, Mateja (Frontiers in Sustainable Cities, 2022)
Research and wider societal debates has explored the potentially transformative role of AI in extended social control and hyper-capitalist development in China. In this paper, we use those debates to reflect on experiments with Urban AI in China. The key issue is whether AI offers something distinctive or different compared with the logics and imaginaries of ideas of the smart city. Analysis of emblematic sites of urban AI management in the cities of Shanghai and Hangzhou demonstrates: the resonances and dissonances between urban AI and smart. But they also demonstrate distinctive and complex landscape of urban AI experiments that is not neatly captured in social control and free market applications perspectives on AI. Moreover, the urban experimental contexts in which AI is being rolled, reveal aspirations for creating new “digital empires,” exploring new limits on data power and potential social resistance. The paper makes a distinctive contribution by providing a new framework for comparing logics of computational urban management in the context of emerging AI applications. As such the paper provides a distinctive framework for situating future applications of urban AI management in China and identifies the future urban research priorities.